Phytoremediation of Cadmium by Native Plants Grown on Mining Soil - Palutoglu, Mahmut; Akgul, Bunyamin; Suyarko, Vasily; Yakovenko, Myroslava; Kryuchenko, Nataliya; Sasmaz, Ahmet (Springer, 2018)
The Gumuskoy mining area is located about 25 km west of Kutahya and is the largest silver deposit in Turkey. The present study investigated translocation and accumulation of cadmium (Cd) from the soil into 11 native plants. Plant and soil samples were collected from the field, and Cd concentrations were analyzed by inductively coupled plasma mass spectroscopy. Mean Cd values in the soil, root, and shoot of native plants in the study area were 82.8 +/- 5, 55.4 +/- 6, and 43.5 +/- 4 mg kg(- 1), respectively. Plants were separated into several groups according to the enrichment coefficients for shoot and root values of plants. These groups showed Carduus nutans and Phlomis could be potentially bioaccumulator plants useful for phytoremediation of mining soils contaminated by Cd.
Keywords: Bioaccumulation; Mining area; Pollution